2017
DOI: 10.1111/jfb.13290
|View full text |Cite
|
Sign up to set email alerts
|

Effect of weight and frontal area of external telemetry packages on the kinematics, activity levels and swimming performance of small‐bodied sharks

Abstract: This study sought to observe the effects of submerged weight and frontal cross-sectional area of external telemetry packages on the kinematics, activity levels and swimming performance of small-bodied juvenile sharks, using lemon sharks Negaprion brevirostris (60-80 cm total length, L ) as a model species. Juveniles were observed free-swimming in a mesocosm untagged and with small and large external accelerometer packages that increased frontal cross-sectional area of the animals and their submerged weight. De… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 52 publications
(120 reference statements)
0
21
0
Order By: Relevance
“…The increases in metabolic rate and decreases in swimming efficiency found here for tagged C. limbatus are generally mirrored by past studies in sharks and teleosts, where tagging has resulted in increased metabolic rates (Burgerhout et al ., ; Lowe et al ., ; Methling et al ., ; Steinhausen et al ., ), increased B T frequency (Bouyoucos et al ., ; Methling et al ., ) and decreased swimming speeds and stride length (Bouyoucos et al ., ; Counihan & Frost, ; Janak et al ., ; Methling et al ., ; Steinhausen et al ., ) in fish carrying externally attached tags compared with control animals. These changes in swimming efficiency with tagging are generally attributed to two main factors: first, that externally attached tags impose increased drag on animals as they swim; second, that the tags increase the negative buoyancy of fish.…”
Section: Measurements and Oxygen Consumption Rates (ṁO2) Of Carcharhimentioning
confidence: 99%
See 2 more Smart Citations
“…The increases in metabolic rate and decreases in swimming efficiency found here for tagged C. limbatus are generally mirrored by past studies in sharks and teleosts, where tagging has resulted in increased metabolic rates (Burgerhout et al ., ; Lowe et al ., ; Methling et al ., ; Steinhausen et al ., ), increased B T frequency (Bouyoucos et al ., ; Methling et al ., ) and decreased swimming speeds and stride length (Bouyoucos et al ., ; Counihan & Frost, ; Janak et al ., ; Methling et al ., ; Steinhausen et al ., ) in fish carrying externally attached tags compared with control animals. These changes in swimming efficiency with tagging are generally attributed to two main factors: first, that externally attached tags impose increased drag on animals as they swim; second, that the tags increase the negative buoyancy of fish.…”
Section: Measurements and Oxygen Consumption Rates (ṁO2) Of Carcharhimentioning
confidence: 99%
“…However, several studies have shown that effects of tagging can still be observed within, or near, this body-mass-tag ratio (reviewed by Bridger & Booth, 2003;Jepson et al, 2005). For example in elasmobranchs, increased energy costs have been reported in scalloped hammerhead sharks Sphyrna lewini (Griffith & Smith 1834) swimming with a tag representing approximately 4% of the body mass of study animals (Lowe et al, 1998) and decreased swimming performance has been shown for lemon sharks Negaprion brevirostris (Poey 1868) carrying tags 1.2-2.4% of their body weight (Bouyoucos et al, 2017b). Conversely, no effects of tagging were observed in juvenile sandbar sharks Carcharhinus plumbeus (Nardo 1827) carrying positively buoyant pop-up satellite archival tags (Lynch et al, 2017).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…spawning, migration, reproduction) for pelagic sharks released from fishing gear but carrying PSATs was probably not detrimental to their health (Jepsen, Thorstad, Havn & Lucas, 2015;Lynch, Marcek, Marshall, Bushnell & Bernal, 2017;Musyl, Domeier et al, 2011). Should PSATs or other tags remain attached for prolonged periods, the possibility exists that extra drag and energetic costs could affect long-term fitness and health outcomes (Bouyoucos, Montgomery, Brownscombe, Cooke & Suski, 2017;Bouyoucos, Suski, Mandelman & Brooks, 2017;Lear, Gleiss & Whitney, 2018), but there was no evidence of increased mortality with time-to-event and the bulk of F r occurred within 40 days of release. Finally, Guida (2016) and Wosnick et al (2019) demonstrated population-level effects in small rays and sharks exposed to fishing, but it remains unresolved whether these findings can be extrapolated to other pelagic elasmobranchs.…”
Section: Mortality Comparisons Of Pelagic Sharksmentioning
confidence: 99%
“…There are a variety of different factors that will determine the type of tag used and individual validation studies are important for determining whether the intended tag is suitable for the target animal. Validation studies are typically designed to observe the effects of tags on swimming kinematics, swimming performance, energy expenditure (measured as oxygen uptake rates) while swimming or at rest, behaviour, or survivorship (Bouyoucos et al ., ; Lefrançois et al ., ; Lowe, ; Makiguchi & Ueda, ; Ross & McCormick, ). It is unclear, however, what constitutes an acceptable level of impairment to the aforementioned metrics due to tagging.…”
Section: Taggingmentioning
confidence: 97%